AHMED YASAWI: LIFE, WORDS AND SIGNIFICANCE IN THE KAZAKH CULTURE - Sala, Renato (Journal of history, 2018)
The article starts analyzing the spiritual aspects of the culture of the Kazakh people, in particular the role played by funerary rituals, pilgrimages, shamanic practices, Islam and Sufism. It proceeds with an introduction to the life, teachings and words of the Sufi master Khoja Ahmed Yasawi (Sayram 1093 AD, Turkestan 1166 AD), underlining the importance, for the Kazakh culture as well as for the entire world, of the Yasawi self-immurement in an underground cell and of the poems (Divan-i Hikmet) transmitted from down there. Finally are analyzed the existing versions of the Divan-i Hikmet, in particular the structure and contents of the 49 hikmet of the Turkestan manuscript of which, as conclusion, is provided a selection of verses translated in English language.